2004
DOI: 10.1021/jo049331a
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Resonance Raman Study of the Triplet States of p-Hydroxyacetophenone and the p-Hydroxyphenacyl Diethyl Phosphate Phototrigger Compound

Abstract: Pico- and nanosecond time-resolved resonance Raman (TR3) spectroscopy have been utilized to study the dynamics and structure of p-hydroxyacetophenone (HA) and the p-hydroxyphenacyl-caged phototrigger compound p-hydroxyphenacyl diethyl phosphate (HPDP) in acetonitrile solution. Transient intermediates were detected and attributed to the triplet states of HA and HPDP. Nanosecond-TR3 measurements were done for two isotopically substituted HA molecules to help better assign the triplet state carbonyl C=O stretchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
60
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 98 publications
(254 reference statements)
14
60
0
Order By: Relevance
“…Based on this, the first species seen in Figure 13.2 (0-1000 ps spectra) is assigned to the HA triplet state. It is interesting to note that a comparison of the triplet spectra here in water solution in Figure 13.2 with those reported in acetonitrile solvent [23] shows some distinct differences in the frequencies of many of the vibrational features as well as spectral profiles of some Raman bands that appear to be indicative of hydrogenbonding effects of the water solvent molecules on the triplet excited state. To distinguish the H-bonded triplet species from the normal free HA triplet species (denoted as 3 HA hereafter), the H-bonded HA triplet species is denoted as 3 HA 0 .…”
Section: Hydrogen-bonding Effects On the Excited States Of Selected Pmentioning
confidence: 81%
See 4 more Smart Citations
“…Based on this, the first species seen in Figure 13.2 (0-1000 ps spectra) is assigned to the HA triplet state. It is interesting to note that a comparison of the triplet spectra here in water solution in Figure 13.2 with those reported in acetonitrile solvent [23] shows some distinct differences in the frequencies of many of the vibrational features as well as spectral profiles of some Raman bands that appear to be indicative of hydrogenbonding effects of the water solvent molecules on the triplet excited state. To distinguish the H-bonded triplet species from the normal free HA triplet species (denoted as 3 HA hereafter), the H-bonded HA triplet species is denoted as 3 HA 0 .…”
Section: Hydrogen-bonding Effects On the Excited States Of Selected Pmentioning
confidence: 81%
“…Examination of Figure 13.2 shows that the 400 nm or 416 nm probe wavelength TR 3 spectra observe two different transient species in water solvent, and this differs from the corresponding TR 3 spectra for HA in acetonitrile solution, where only one transient determined to be the triplet state of HA was seen [23]. A femtosecond-time-resolved fluorescence (fs-TRF) investigation found that, for HA and p-HP phototrigger compounds, the intersystem crossing (ISC) rates are extremely fast, with time constants of about 1-2 ps, with the conversion rates in water and water-mixed acetonitrile being similar to those measured in neat acetonitrile [24].…”
Section: Hydrogen-bonding Effects On the Excited States Of Selected Pmentioning
confidence: 83%
See 3 more Smart Citations